COMMUNITY PERCEPTION RELATIONSHIP WITH ANXIETY LEVEL WHEN RECEIVING THE COVID-19 BOOSTER VACCINATION IN KUTAMANEUH VILLAGE IN 2022 - Enung, Enung Nuraeni; Pelawi, Arabta M. Peraten; Simamora, Rotua Suriany (Rena Cipta Mandiri, 2024)
The Covid-19 vaccination is one of the government's efforts in dealing with the Covid-19 problem. The Covid-19 vaccination aims to create herd immunity. In the implementation of the Covid-19 vaccination, there were various obstacles such as rejection from the community, fear of the impact of vaccination (KIPI), the circulation of hoaxes related to vaccination, and so on. People's perceptions will influence their attitude towards the vaccine itself. Finally, it will affect people's behavior towards vaccines. There are many pros and cons related to vaccination programs that make people feel anxious and afraid to get the Covid-19 vaccine. The public's anxiety and fear will indirectly hinder the achievement of the Covid-19 vaccination program target. The design in this study uses Analytical Observation with a Cross-Sectional research design, the sampling technique used in this study is a probability sampling technique of simple random sampling type with a sample of 146 respondents, measured using a questionnaire and carried out statistical tests using Chi-Square. Based on the results of statistical analysis using the Chi-Square test with a significance level of 95%, the results obtained a p-value (0.001) < value (0.05) so that it can be stated that H0 is rejected with the conclusion